tRNA Derived smallRNAs: smallRNAs Repertoire Has Yet to Be Decoded in Plants - Sablok, Gaurav; Yang, Kun; Chen, Rui; Wen, Xiaopeng (Frontiers in Plant Science, 2017)
Among several smallRNAs classes, microRNAs play an important role in controlling the post-transcriptional events. Next generation sequencing has played a major role in extending the landscape of miRNAs and revealing their spatio-temporal roles in development and abiotic stress. Lateral evolution of these smallRNAs classes have widely been seen with the recently emerging knowledge on tRNA derived smallRNAs. In the present perspective, we discussed classification, identification and roles of tRNA derived smallRNAs across plants and their potential involvement in abiotic and biotic stresses.